Negotiating from the margins dynamics of women's work in a globalized agricultural economy - Dungo, Nanette Garcia (University of the Philippines Press, 2007)
"This book examines how the present globalized worksites are opening channels for women to break out from their traditional confinement at home. Through subcontracting, a type of employment that offers flexibility in working hours and workplace, the women are able to contribute to the household income. But with the women prioritizing paid work over domestic chores, the traditional division of labor at home is disrupted, causing conflict between husbands and wives.The book focuses on the women's various response to their husbands' ambivalent attitude toward their rising participating in productive work. As women workers constantly engage in negotiation, compromise, or contestation, they are in the process crafting a new narrative of their own selves, utilizing more empowering initiatives mediating between the demands of tradition and those of globalizing structures."--Back cover.